Multi‐species outbreak of SARS‐CoV‐2 Delta variant in a zoological institution, with the detection in two new families of carnivores. Issue 5 (26th July 2022) - Allender, Matthew C.; Adkesson, Michael J.; Langan, Jennifer N.; Delk, Katie W.; Meehan, Thomas; Aitken‐Palmer, Copper; McEntire, Michael M.; Killian, Mary L.; Torchetti, Mia; Morales, Shirley A.; Austin, Connie; Fredrickson, Richard; et al.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has a worldwide distribution in humans and many other mammalian species. In late September 2021, 12 animals maintained by the Chicago Zoological Society's Brookfield Zoo were observed with variable clinical signs. The Delta variant of SARS‐CoV‐2 was detected in faeces and nasal swabs by qRT‐PCR, including the first detection in animals from the families Procyonidae and Viverridae. Test positivity rate was 12.5% for 35 animals tested. All animals had been vaccinated with at least one dose of a recombinant vaccine designed for animals and all recovered with variable supportive treatment. Sequence analysis showed that six zoo animal strains were closely correlated with 18 human SARS‐CoV‐2 strains, suggestive of potential human‐to‐animal transmission events. This report documents the expanding host range of COVID‐19 during the ongoing pandemic.